PEMANFAATAN CITRA PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS UNTUK PEMETAAN TANAH SEMI DETIL DI DAERAH ALIRAN SUNGAI MORAMO, SULAWESI TENGGARA - , JUFRI KARIM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to assess the ability of ALOS AVNIR-2 imagery for land identification elements (landforms, topography, lithology, landuse/natural vegetation) that is used for semi-detailed soil mapping